Short transient recovery of low voltage-grid-tied DC distributed generation - Harirchi, F.; Simoes, M.; Durra, A.; Muyeen, S.M. (2015)
This paper presents a design framework for a power electronic interface for a grid-tied (GT) low voltage DC distributed generation (DG) with short transient recovery between GT mode and islanding mode. The proposed interface contains controlled unidirectional and bidirectional floating interleaved converters (FIC), in addition to a smart grid-tied inverter (GTI) to optimize the overall performance of the DG from different perspectives and provide compatible AC voltage to the grid and local loads during islanding mode, GT operating mode and transition mode. FIC has been applied in order to address the low gain issue in photovoltaic (PV) based DGs, and bidirectional FIC is used in order to add the Energy Storage Unit (ESU) to the system. A comprehensive study on bidirectional FIC operating modes indicates that a single-controller scheme can be applied to control the overall operation of this converter in the buck and boost modes. By using this method, the transient response caused by changing controllers between the boost and buck modes will be recovered. Finally, a battery lifetime management algorithm is proposed for increasing the storage system reliability. The effectiveness of the proposed framework has been verified using simulation results in MATLAB and PSIM software; experimental work is under progress.